190 TAPASIN AND HLA CLASS I DOWN-REGULATED IN PRIMARY HUMAN MULTIPLE MYELOMA: SUITABLE INDICATOR OF POOR PROGNOSIS. (1st January 2006) - Vélez, B.; Grizzi, F.; Wenhan, W.; Pinkston, J.; Cunha, N. D.; Cobos, E.; Kast, W. M.; Ferrone, S.; Chiriva-Internati, M.
Abstract : Purpose: The correlation between expression of tapasin and HLA class I was studied in patients refractory to conventional treatment in multiple myeloma (MM). Regulation of tapasin and HLA class I expression could be suitable markers for prognostic factors of MM patients. Methods: Expression of mRNA for tapasin and HLA class I was evaluated via reverse transcription-polymerase chain reaction (RT-PCR) for 20 primary MM tumors and 6 MM cell lines. Protein analysis was performed using Western blots for protein expression of tapasin and HLA class I. Summary: HLA class I and tapasin were analyzed in a panel of 20 fresh primary MM tumors and 6 MM cell lines. In primary tumors, 50% do not express tapasin at the protein level but are positive for mRNA. Following standard treatment of MM, 50% do not express tapasin at the protein level and 30% do not express mRNA or protein. Restoration by IFN-g further suggests tapasin expression in MM is alternately due to dysregulation rather than structural alterations by mutation. Conclusion: These data indicate that absence of tapasin plays a central role in down-regulation of HLA class I in relapse MM patients. Tapasin and HLA class I down-regulation was prominent in relapsing patients compared to control. Deficiency of tapasin in tumor cells appears to be a frequent event in human tumors. Furthermore, tapasin and HLA class I down-regulation in MM was extensively associated with reduced survival of patients, therefore playing a role in poor prognosis of disease.